The Unfair Sentencing Act: Racial Disparities and Fiscal Consequences of America's Drug Laws - Zimmerman, Kristin (2014)
In 1986, the United States government attempted to combat the perceived war on drugs by enacting mandatory drug laws, with a primary focus on incarcerating crack offenders. The result of this was a mass influx of African Americans to US penitentiaries and minimal to zero reduction of crack convictions. Because the Anti-Drug Abuse Act of 1986 recognized 100 grams of cocaine as equivalent to one gram of crack, it has been perceived not as a war on drugs, but as a war on a war on minorities. The mass incarceration of drug offenders also led to severely damaging fiscal consequences that were forced onto the nation’s taxpayers. In November 2010, President Obama signed the Fair Sentencing Act, which decreased the imbalanced ratio of 100:1 to 18:1. The Fair Sentencing Act, named by the United States government, is still unfair. Until Congress and the Sentencing Commission agree that one gram of cocaine is equivalent to one gram of crack, justice has not been served